Sysml 4 Digital Twins – Utilization of System Models for the Design and Operation of Digital Twins. (May 2022) - Wilking, F.; Sauer, C.; Schleich, B.; Wartzack, S.
Abstract: The implementation of Digital Twins has become a common task for many industrial companies to ensure a sufficient digitization of their products and maintain competitiveness. This results in the question of how to compensate additional effort caused by designing Digital Twins. With this paper, an approach for this compensation is presented by creating Digital Twin behaviour through utilizing SysML diagrams and directly derivate usable code from them for a further implementation. This offers a part solution of lowering the threshold for using MBSE and increasing its benefits.